SISTEM INFORMASI DISTRIBUSI BARANG PADA PT. CAMPINA INDUSTRI (Information Technology and Telematics, 2013)
Distribution system design information on PT. Industry Campina based on data issues related to the distribution goes on PT. Industry Campina not neatly arranged and are still using manual systems are still not integrated and the data between the parties, such as recording the distribution of goods, evidence of transactions recorded delivery still using manual systems. Resulting in wastage of time in searching and checking data report generation or distribution of goods distribution of goods that still seems slow. The objectives to be achieved is to create a system of information distribution in PT. Industry Campina who can handle the problem of distribution of goods faced by the company. Campina IndustryKeywords - Information Systems, Distribution